The elephant man [videorecording (DVD)] - Lynch, David, 1946-; Lynch, David, 1946-; Hopkins, Anthony, 1937-; Hurt, John, 1940-2017; Bancroft, Anne, 1931-2005; Jones, Freddie, 1927-2019-; Treves, Frederick, 1853-1923; Montagu, Ashley, 1905-1999 (Widescreen DVD collection., 2001)
Based on a true story, the film examines the complex emotional experiences faced by John Merrick, the "Elephant Man" when he is discovered by a dedicated surgeon. Rescued from his degrading life as a circus freak, Merrick is given a chance to live his last years with comfort, respect, and dignity.